Strengthening Fenton-like reactions to improve lignocellulosic degradation performance by increasing lignocellulolytic enzyme core microbes during rice straw composting - Wu, Di (Waste management (New York, N.Y.), 2023)
Copyright © 2023 Elsevier Ltd. All rights reserved.